Face the consequences: Learning about victim's suffering reduces sexual harassment myth acceptance and men's likelihood to sexually harass. Issue 6 (30th July 2014) - Diehl, Charlotte; Glaser, Tina; Bohner, Gerd
<x xml:space="preserve">Abstract</x> Prior research has shown that (1) better knowledge about the consequences of rape goes along with less rape‐supportive attitudes and lower rape proclivity, and (2) empathy with the victims correlates negatively with sexual aggression. In two experiments, the authors combined these approaches in order to reduce sexual harassment myth acceptance (SHMA) and the likelihood to sexually harass (LSH). In Study 1, 101 male and female university students read a report describing sexual harassment as either serious or harmless, and completed scales assessing dispositional empathy and SHMA. Results showed that higher empathy was associated with lower SHMA; furthermore, learning about the seriousness (vs. harmlessness) of sexual harassment led to lower SHMA, particularly in participants low in empathy. Gender differences in SHMA were fully explained by gender differences in empathy. In Study 2, perspective taking, a crucial aspect of empathy, was manipulated. One hundred nineteen male and female participants read either a neutral text or a description of a sexual harassment case, which was written either from the female target's or from the male perpetrator's perspective; then they completed scales measuring SHMA and (only male participants) LSH. The target's perspective led to lower SHMA and to lower LSH than did the neutral text, whereas no such effect was found for the perpetrator's perspective. Implications for intervention programs are discussed. Aggr. Behav. 40:489–503, 2014. © 2014 Wiley Periodicals, Inc.